Fabrication Of Conductive Ink Based On Graphene Nanoparticles - Wahid, Amira Fitriyanie Abd (Universiti Sains Malaysia, 2017)
The main objective of this project was to fabricate stretchable graphene conductive ink. The stretchable printed package was prepared by using graphene nanoparticles as conductive ink. The stretchable printed package consist of two components which is stretchable substrate and conductive ink. The stretchable substrate was prepared using polysiloxane. In order to make the graphene conductive ink stretchable with good conductivity, specific ingredients like high molecular weight polydimethylsiloxane-hydroxide (PDMS-OH) and tin catalyst was added. In this project, four samples of stretchable printed package that contain different concentration of graphene (15%, 20%, 25% and 30%) is prepared. Then, the electrical properties of the graphene printed package sample prepared was studied. The electrical properties that was studied were conductivity and resistivity of the sample during normal and stretched condition. Besides that, chemical structure, mechanical properties and thermal properties of the printed package were also studied. The results revealed that sample that contain 20% weight percentage of graphene has the highest stretchability with good conductivity while sample with the highest concentration of graphene which is 30% has the highest conductivity during unstretched condition but its stretchability is very poor that cause decreased in conductivity during stretch condition.